OWNED MEDIA: SYSTEMATIC LITERATURE REVIEW (SLR) - Fian Arifiona Faradila; Indri Safitri; Herlina Kusuma Wardhani (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
E-marketing communications offer a great way to establish and enhance connections with customers. In this digital realm, there are various key strategies to consider. One of them is delivering relevant and captivating content that truly resonates with the target audience. Another strategy involves encouraging internet users to engage with the content by leaving comments, sharing their own content, or even participating in interactive games provided by the company. The main objective of this study is to gain a deeper understanding of the knowledge, characteristics, and impact of owned media on digital marketing. To conduct this research, the Preferred Reporting Items for Systematic Review and Meta Analysis related to owned media were utilized. Data was collected from multiple journal sites indexed in Scopus over a span of six years. The findings of this study reveal that having a large social media following does not necessarily translate to increased sales. In fact, owned social media platforms tend to be more effective for brands with a smaller number of followers. Additionally, while it may be tempting to adopt a one-size-fits-all global social media strategy, it is crucial to take into account the cultural context of each country. In countries with a high power distance, a more nuanced approach is required for owned social media to be truly effective. This research contributes to a better understanding of the functions of social media and provides valuable insights for developing effective marketing strategies.